Pengaruh Harga, Lokasi, Dan Fasilitas Terhadap Loyalitas Pelanggan Warung Kopi : Studi Kasus Warung Kopi Di Jalan Letda Sujono - Banjirul Akbar; Marliyah Marliyah; Rahmi Syahriza (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study seeks to examine and assess the extent and impact of price, location and facilities on customer loyalty in coffee shops. Specifically, it focuses on a coffee shop located on Jalan Letda Sujono in Medan Tembung District. Using a quantitative descriptive approach, this research uses primary data collected from respondents. The research subject was a coffee shop on Jalan Letda Sujono, while the object of analysis consisted of 95 customers of the RGR KOPI shop. To analyze the data, SPSS 20.0 was used for classical assumption testing, multiple regression analysis, and hypothesis testing. Findings from hypothesis testing, especially the t-test, show that there is a significant and positive influence of price on customer loyalty at the Coffee Shop on Jalan Letda Sujono, Medan Tembung District, with a t value of 2.794. This value is greater than the t table (1.65291) with a t sig value (0.006) < 0.05. Location has a significant and positive effect on customer loyalty at the coffee shop on Jalan Letda Sujono, Medan Tembung district. The calculated value is 2.059. This value is greater than the t table (1.65291) with a t sig value (0.003) < 0.05. Facilities have a significant and positive effect on Customer Loyalty of the Coffee Shop on Jalan Letda Sujono, Medan Tembung District, the t-count value is 6.257. This value is greater than the t table (1.65291) with a t sig value (0.000) < 0.05. Price (X1), Location (X2), Facilities (X3) have a significant and positive effect on Customer Loyalty of the Coffee Shop on Jalan Letda Sujono, Medan Tembung District. This value is greater than F table (2.26) with an F sig value (0.000) < 0.05 . The test results for the variables Price (X1), Location (X2), Facilities (X3) contributed 61.4% to the Customer Loyalty variable.